Pengaruh Metode Latihan Kanga Escape Terhadap Kebugaran Jasmani Siswa Kelas III Sekolah Dasar Negeri Wajasari Kecamatan Adimulyo Kabupaten Kebumen - Damaiyanti, Yustiana; Syarif, Ahmad; Prabowo, Bangkit Yudho; Erfayliana, Yudesta (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research was motivated by the low results of students' physical fitness tests in PJOK subjects because students felt bored with monotonous learning methods. Quantitative research methods are pre-test, treatment and post-test. The subjects in this research were the lowerclass students of Wajasari State Elementary School, Adimulyo District, Kebumen Regency, class III, totaling 14 children, namely 4 boys and 10 girls. Data collection techniques in this research used observation, documentation and tests. Data analysis techniques regarding the effect of the kanga escape training method on students' physical fitness used descriptive statistics expressed in percentages.The results of research on low class students' physical fitness data using the Indonesian Physical Fitness Test (TKJI) obtained initial data (pre-test) with a medium classification of 6 students (43%), 5 students (36%) with poor classification, and 3 good classifications. students (21%). And the final test (post-test) had a good classification of 7 students (50%), 3 students (21%) with a medium classification, 2 students (14%) with a very good classification, and 2 students (14%) with a poor classification. Thus, there is an increase in students' physical fitness after being treated with the kanga escape training method.